Effect of low-load hamstring strength training on the H/Q ratio and electromyographic activity in various gymnastic actions in young aesthetic group gymnasts - Jokelainen, Opri (2013)
Muscle balance is an important factor for decreasing injury risks among sports, as weak ago-nist-antagonist strength ratio may predispose to injuries. Hamstring-to-quadriceps (H/Q) strength ratio has been studied in several sports in order to describe the muscular balance of thighs. During pubertal longitudinal growth, hamstrings may be weaker due to the mechanical stress of growth. As both hamstring flexibility and knee extension strength are important for aesthetic group gymnastics (AGG), the H/Q strength ratio might be expected to be low among this sport. Describing muscle activation patterns of hamstrings and quadriceps femoris in AGG actions is efficient for determining the H and Q activities and relations in different movements. Neural effects of low-load hamstring strength training on these muscle activities were studied to determine if strength training, in order to improve muscle balance, affects performance or muscle activities in performance.